2019
DOI: 10.1002/jctb.6292
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity of Yb, Er, Ce‐codoped TiO2 for degradation of Rhodamine B and 4‐chlorophenol

Abstract: BACKGROUND Photodegradation through an advanced oxidation process gives promising prospects for environmental protection. Although titanium dioxide (TiO2) is considered as an excellent photonic material candidate, however, the band gap of TiO2 is 3.2 eV which limits its effective applications. Various approaches have been developed for enhancing the utilization of TiO2 such as coupling with other narrow bandgap semiconductors and metal ions. We developed a novel ytterbium (Yb), erbium (Er), cerium (Ce)‐codoped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…26 TiO 2 codoped with Yb/Er/Ce displayed efficient photocatalytic performance for the elimination of 4chlorophenol (4-CP) and RhB. 14 Ce, Er, and Yb ions acted as electron mediators during electron transfer from TiO 2 , promoting effective separation of photogenerated carriers. β-Bi 2 O 3 exhibited excellent performance in NO removal after combination with CeO 2−δ , which was due to the strengthened visible light adsorption and the fast separation of electron− pole pairs because of the oxygen vacancies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…26 TiO 2 codoped with Yb/Er/Ce displayed efficient photocatalytic performance for the elimination of 4chlorophenol (4-CP) and RhB. 14 Ce, Er, and Yb ions acted as electron mediators during electron transfer from TiO 2 , promoting effective separation of photogenerated carriers. β-Bi 2 O 3 exhibited excellent performance in NO removal after combination with CeO 2−δ , which was due to the strengthened visible light adsorption and the fast separation of electron− pole pairs because of the oxygen vacancies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The core of photocatalytic technology is the photocatalyst, and many materials can act as a photocatalyst [5]. Table 1 shows the published data of different photocatalysts, including TiO 2 [6][7][8], SrTiO 3 [9][10][11], ZnO [12][13][14], WO 3 [15][16][17], ZrO 2 [18][19][20], and g-C 3 N 4 [21][22][23], and their performance. Among these photocatalysts, TiO 2 occupies an important position due to its stable 2 of 32 physical and chemical properties, strong oxidation capacity, high photocatalytic activity, and excellent biocompatibility [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Amount difference candidates for preparation of hybrid carbon‐based materials, titanium dioxide is a particular candidate for the preparation of photosensitive structures because this metal oxide is known for its promising photocatalytic abilities 24‐26 . In this line, many research studies have been reported on the preparation and photocatalytic ability of titanium dioxide and its hybrid materials 27‐33 …”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] In this line, many research studies have been reported on the preparation and photocatalytic ability of titanium dioxide and its hybrid materials. [27][28][29][30][31][32][33] In recent years, titanium dioxide nanotubes have attracted much attention because of their unique shape and properties. 34,35 Surely, the preparation of its hybrids with carbon-based materials could reach us to both of the advantage of titanium dioxide nanotubes and carbon material.…”
mentioning
confidence: 99%